2018
DOI: 10.1038/s41556-018-0056-9
|View full text |Cite
|
Sign up to set email alerts
|

Daughter-cell-specific modulation of nuclear pore complexes controls cell cycle entry during asymmetric division

Abstract: The acquisition of cellular identity is coupled to changes in the nuclear periphery and nuclear pore complexes (NPCs). Whether and how these changes determine cell fate remains unclear. We have uncovered a mechanism regulating NPC acetylation to direct cell fate after asymmetric division in budding yeast. The lysine deacetylase Hos3 associates specifically with daughter cell NPCs during mitosis to delay cell cycle entry (Start). Hos3-dependent deacetylation of nuclear basket and central channel nucleoporins es… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 69 publications
7
65
0
1
Order By: Relevance
“…(Rb protein in humans) (Kumar et al, 2018). Our data in the FXR1-deficient cells show accumulation of cells with phosphorylated nuclear Rb (P-Rb) ( Figure 7E, F), which supports the speculation that FXR1-dependent G1 regulation could be due to specific effects on P-Rb export.…”
Section: Discussionsupporting
confidence: 84%
“…(Rb protein in humans) (Kumar et al, 2018). Our data in the FXR1-deficient cells show accumulation of cells with phosphorylated nuclear Rb (P-Rb) ( Figure 7E, F), which supports the speculation that FXR1-dependent G1 regulation could be due to specific effects on P-Rb export.…”
Section: Discussionsupporting
confidence: 84%
“…Hos3 binds to the daughter-cell side of the septin ring, a cytoskeletal structure that assembles at the bud neck (Wang and Collins, 2014). Hos3 then transiently associates with the periphery of the daughter cell nucleus during anaphase chromosome segregation (Kumar et al, 2018). Since the yeast NE does not disassemble during mitosis, NPCs destined to the bud are in close proximity with the bud neck during anaphase.…”
Section: Nuclear Pore Deacetylation Regulates Gene Expression In Buddmentioning
confidence: 99%
“…Recent work from our laboratory revealed that in budding yeast, an enzyme that deacetylates nuclear pore complexes acts as a cell fate determinant in daughter cells (Kumar et al, 2018). Nuclear pore complexes (NPCs) are multi-protein assemblies that forms channels in the nuclear envelope thus connecting the nucleus and cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, artificial tethering of reporter genes to subtelomeric regions and to the nuclear periphery can lead to their silencing [16][17][18][19]. Moreover, perinuclear tethering of the CLN2 cyclin gene in daughter cells mediates its silencing during the G1 phase [20]. The association of silent information regulators (SIR) factors with telomeres also contributes to perinuclear repression [19].…”
Section: Introductionmentioning
confidence: 99%